Diseño de un modelo de gestión por procesos para la Empresa Municipal Mancomunada de Aseo Integral de los Cantones 24 de Mayo, Santa Ana y Olmedo “EMMAI-MANABI-CS-EP”, Año 2013 - Gómez Macías, Rosa Mercedes (2014)
This end of degree work, develops a proposal for design of process management for the enterprise public Municipal joint of the cantons may 24, Santa Ana and Olmedo, serving public toilet in the field regional Commonwealth Center South of Manabí, having as main objective improve the quality of services offered by the area of Social coordination and attention to citizenship through the design of a model of management by Processes. The Constitution of the Republic of Ecuador, Public Enterprises Act of Ecuador, Transparency Act and the objectives of the National Plan of good living guarantee the rights of nature, and promote a healthy and sustainable environment. With process management will ensure that the activities planned in the time provided, have the material and logistical resources to fulfill them, achieving efficiency in training and communication to the target audience. On the other hand a proposal for Process Management in the area of social management is provided, allowing you to measure the performance indicators. To give clarity to management for pooled processes is required the implementation of a basic regulation process for the Company public Municipal joint of the cantons may 24, Santa Ana and Olmedo, so that within the proposal is the proposal of the organic regulations for the entire institution.